No Excess Total Mortality in Italy in the First Semester of 2023 at All Ages and in the Working Age Population - Alicandro, Gianfranco; Gerli, Alberto; Santucci, Claudia; Centanni, Stefano; Remuzzi, Giuseppe; La Vecchia, Carlo (La Medicina del Lavoro, 2023)
Background: Italy experienced a sustained excess in total mortality between March 2020 and December 2022, resulting in approximately 226,000 excess deaths. This study extends the estimate of excess mortality in the country until June 2023, evaluating the persistence of excess mortality. Methods: We used mortality and population data from 2011 to 2019 to establish a baseline for expected deaths during the pandemic. Over-dispersed Poisson regression models were employed, stratified by sex, to predict expected deaths. These models included calendar year, age group, and a smoothed function for the day of the year as predictors. Excess mortality was then calculated for all ages and working ages (25-64 years). Results: From January to June 2023, we found a reduction in the number of deaths compared to the expected ones: 6,933 fewer deaths across all age groups and 1,768 fewer deaths in the working age category. This corresponds to a 2.1% and 5.2% decrease in mortality, respectively. Conclusions: The excess mortality observed in Italy from March to December 2022 was no longer observed in the first six months of 2023.